Toluene Dioxygenase‐Catalysed Oxidation of Benzyl Azide to Benzonitrile: Mechanistic Insights for an Unprecedented Enzymatic Transformation. (21st January 2016) - Vila, María Agustina; Pazos, Mariana; Iglesias, César; Veiga, Nicolás; Seoane, Gustavo; Carrera, Ignacio
Abstract: Enzymatic dioxygenation of benzyl azide by toluene dioxygenase (TDO) produces significant amounts of the cis ‐cyclohexadienediol derived from benzonitrile, along with the expected azido diols. We demonstrate that TDO catalyses the oxidation of benzyl azide to benzonitrile, which is further dioxygenated to produce the observed cis ‐diol. A proposed mechanism for this transformation involves initial benzylic monooxygenation followed by a nitrene‐mediated rearrangement to form an oxime, which is further dehydrated to afford the nitrile. To the best of our knowledge, this is the first report of enzymatic oxidation of an alkyl azide to a nitrile. In addition, the described oxime‐dehydration activity has not been reported for Rieske dioxygenases. Abstract : Toluene dioxygenase catalyzes the oxidation of benzyl azide to benzonitrile. A plausible mechanism involves initial benzylic monooxygenation followed by nitrene‐mediated rearrangement to form an oxime, which is dehydrated to afford the nitrile. To the best of our knowledge, this is the first report of enzymatic oxidation of an alkyl azide to a nitrile.